(untitled) (Biological Sciences - PJSIR, 2025)
In this study, the growth of three lactic acid bacteria in cereal substrates of maize, sorghum and malt were evaluated. Molecular analysis was used to characterize the organisms and their probiotic abilities ascertained. After 48 h of fermentation, the viable counts revealed that L. fermentum had a count of 6.21 log Cfu/mL, L. plantarum had a count of 6.62 Cfu/mL and L. nantensis had a count of 7.51 Cfu/mL in maize substrate. The counts for L. fermentum, L. plantarum and L. nantensis in the sorghum substrate were 4.66, 8.77 and 9.36 log Cfu/mL respectively, whereas the viable counts for malt fermentation were 8.05, 8.92 and 9.42 log Cfu/mL for L. fermentum, L. plantarum and L. nantensis, respectively. This research therefore suggests that cereals (maize, sorghum and malt) are suitable for the growth of the three probiotic strains being L. fermentum, L. plantarum and L. nantensis.